Synthesis and Spectral Studies of Heterocyclic Azo Dye Complexes with Y(III) and La(III)Ions. - Suhad Shakir (Al-Qadisiyah Journal of Pure Science, 2017)
Coupling reaction of 4-amino antipyrine with 2,6-dimethyl phenol gave bidentate azo ligand. The prepared ligand was identified by Microelemental Analysis, 1HNMR, FT-IR and UV-Vis spectroscopic techniques. Treatment of the prepared ligand with the following metal ions (YIII and LaIII) in aqueous ethanol with a 1:3 M:L ratio and at optimum pH, yielded a series of neutral complexes of the general formula [M(L)3]X3 (X= Cl or NO3). The prepared complexes were characterized using flame atomic absorption, (C.H.N) Analysis, FT-IR and UV-Vis spectroscopic methods as well as conductivity measurements. The nature of the complexes formed were studied following the mole ratio and continuous variation methods, Beer's law obeyed over a concentration range (1Ã—10-4 - 3Ã— 10-4 M). High molar absorbtivity of the complex solutions were observed. From the obtained data the tetrahedral structure was suggested for all prepared complexes.